New Onset of Diabetes Mellitus and Associated Factors among COVID-19 Patients in COVID-19 Care Centers, Addis Ababa, Ethiopia 2022 - Asaminew Habtamu Sane; Migbar Sibhat Mekonnen; Melsew Getnet Tsegaw; Wuletaw Chane Zewde; Edmialem Getahun Mesfin; Hailu Asmare Beyene; Taye Mezgebu Ashine; Kasie Gebeyehu Tiruneh; Melkie Ambaw Mengistie (Journal of Diabetes Research)
Introduction. New onset of diabetes mellitus was noted as the commonest comorbidity in the COVID-19 pandemic, which contributed to a worse prognosis. Existing evidence showed that new-onset diabetes is associated with increased mortality compared to nondiabetic and known diabetic patients in the COVID-19 era. SARS-CoV-2 virus can worsen existing diabetes; at the same time, it can trigger new-onset diabetes that eventually worsens patient outcomes. Thus, this study is aimed at determining the prevalence and factors associated with new onset of diabetes mellitus among COVID-19 patients. Methods. Institution-based retrospective cross-sectional study design was conducted by reviewing 244 patient’s records in the Addis Ababa COVID-19 care center. Descriptive statistics and binary logistic regression were used. During bivariate analysis, variables with p≤0.25 were transferred into multivariate analysis. Adjusted odds ratios to determine the strength and presence of the association with a 95% confidence interval and p value ≤ 0.05 were considered, respectively. Results. The mean age of the study participants was 53.2 years with (SD=13.35). The study findings showed that 31.1% (CI: 25.4-37.4) of COVID-19 patients had new onset of diabetes mellitus; of those, 11.8% had type 1 and 88.2% had type 2 diabetes. Being male (aOR=2.9; 95% CI: 1.2, 7.1), family history of hypertension (aOR=3.7; 95% CI: 1.3, 10.5), obesity (aOR=3.1; 95% CI: 1.01, 8.9), having pulmonary embolism (aOR=0.2; 95% CI: 0.06, 0.04), and hyperkalemia (aOR=9.3; 95% CI: 1.8, 47.3) showed statistically significant association with new onset of diabetes mellitus. Conclusion. A significant proportion of COVID-19 patients had been diagnosed with new onset of diabetes mellitus, and new-onset type 2 diabetes mellitus is the most common diabetes mellitus type. Being male, obesity, having a pulmonary embolism, family history of hypertension, and hyperkalemia were independently associated with new onset of diabetes mellitus among COVID-19 patients. Therefore, focused interventions need to be strengthened towards the identified factors.